2021
DOI: 10.2306/scienceasia1513-1874.2021.025
|View full text |Cite
|
Sign up to set email alerts
|

Flooding overshadows phosphorus availability in controlling the intensity of arbuscular mycorrhizal colonization in Sangyod Muang Phatthalung lowland indica rice

Abstract: Phosphorus (P) availability and soil water are two important environmental factors in lowland rice paddies. They limit the ability of rice to form mutualistic associations with arbuscular mycorrhizal fungi (AMF). The dynamics of this symbiotic interaction are intensified by phosphorus deficiency and attenuated by anaerobic conditions. However, the effects of combined phosphorus deficiency and anaerobic conditions on AMF symbiosis in paddy soil were unproven. The main objective of this study is to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 41 publications
0
15
1
Order By: Relevance
“…Our previous study showed that flooding plays a major role in shaping fungal communities and significantly reduced AMF colonization and AMF abundance in the roots of the SMP landrace rice variety grown in organic rice paddy soil. Only eight amplicon sequence variants of the fungal ITS sequences belonged Glomeraceae, which seems to underestimate the total AMF species in the study site [5]. Moreover, the molecular identification of AMF at the genus or species level by the ITS region is limited.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…Our previous study showed that flooding plays a major role in shaping fungal communities and significantly reduced AMF colonization and AMF abundance in the roots of the SMP landrace rice variety grown in organic rice paddy soil. Only eight amplicon sequence variants of the fungal ITS sequences belonged Glomeraceae, which seems to underestimate the total AMF species in the study site [5]. Moreover, the molecular identification of AMF at the genus or species level by the ITS region is limited.…”
Section: Introductionmentioning
confidence: 86%
“…Genomic DNA samples of roots of Sangyod Muang Phatthalung (SMP) rice plants grown in non-flooded and flooded conditions for 6 weeks were obtained from our previous study [5]. To identify the 1.5-kb SSU-ITS-LSU sequences of AMF present in the roots, nested PCR was run with Kruger primers [21].…”
Section: Determination Of Amf In Rice Rootsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Klinnawee et al [ 42 ] have documented that under water-saturated soil conditions, the symbiotic relationship between mycorrhizal fungi and lowland (flooded) rice plant roots is diminished because, as aerobic microbes, these organisms similar to other fungi are greatly affected by the amount of water in the soil, which determines the availability of oxygen. ITS2 sequencing analysis has shown that keeping rice paddies inundated inhibits the extent of fungal communities in the soil and reduces the abundance of mycorrhizal fungi in rice roots [ 42 ].…”
Section: The Diverse and Dynamic Structures Of Rice Microbiomesmentioning
confidence: 99%